1995
DOI: 10.1002/apmc.1995.052250104
|View full text |Cite
|
Sign up to set email alerts
|

Faser‐Matrix‐Haftung in Kunststoffverbunden aus thermoplastischer Matrix und Flachs, 2. Die anwendung von funktionalisiertem polypropylen

Abstract: ZUSAMMENFASSUNG SUMMARY:Adhesion of flax fibres to a polypropylene matrix in flax/PP composites was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…The results from [5] indicated that the measured s G can be increased by the use of MAH-PP up to 100 %. According to Eq.…”
Section: Mah-content In the Adhesive (Mg Koh/g) Changing Tensile Strementioning
confidence: 81%
See 1 more Smart Citation
“…The results from [5] indicated that the measured s G can be increased by the use of MAH-PP up to 100 %. According to Eq.…”
Section: Mah-content In the Adhesive (Mg Koh/g) Changing Tensile Strementioning
confidence: 81%
“…The tensile parameters also increased significantly. [5] Possibilities of adding adhesives within different composite technologies: Considering the practical industrial conditions all processes that require a separate wet fibre pre-treatment cannot be utilized because of economical reasons. Particularly this is true of adhesive systems that must be applied by organic solvents.…”
mentioning
confidence: 99%
“…Flax fibre-reinforced PP composites have attracted much attention [209][210][211] . The results of a research project of a German company (Daimler-Benz A. G.) suggests 212) that flax and sisal based composites are used for making vehicle interior parts.…”
Section: Flax Hemp and Ramie Based Biocompositesmentioning
confidence: 99%
“…Special ne and clean bers can be produced by the Reutlingen steam-explosion process (STEX) [5 -7]. The hydrophilicity of the bers can be reduced by chemical modi cation or by hydrophobic surface nishes and is also in uenced by the application of adhesion promoters [1,[7][8][9][10][11]. Silane treatment, has been found to be very effective ( [1] and Table 1 [8]).…”
Section: Introductionmentioning
confidence: 99%